José Carlos Mariátegui: Between cultural policies and cultural management - Vich, Victor (2023)
This essay explores José Carlos Mariátegui's facet as an observer of state cultural policies and as a cultural manager from civil society. Mariátegui was a tireless founder of newspapers and magazines, and promoted a type of editorial production that was marked by novel models of sustainability and dissemination. His aim was both to contribute to transforming culture understood as a "way of life" and to propose editorial projects aimed at forming more informed citizens, with new ideas and a different sensibility from that proposed by capitalist society. For this reason, this article explores this little-studied facet of José Carlos Mariátegui's work based on his journalistic practice, his work in the publishing field -which included the creation of the Minerva publishing house and the sustainability models of Amauta and Labor-, and his incessant concern for cultural policies in Peru (understood as instances of democratization of culture). As a result, he organized an extensive network of contacts to ensure an efficient system of dissemination. We argue that Mariátegui was not only the one who produced the most original thought of Peruvian modernity, but he was also a dynamic cultural agent in search of significant transformations in the country.